Successful combination therapy of cyclosporine and methotrexate for refractory polymyositis with anti-Jo-1 antibody: a case report. - Chang, Hyun Kyu (Korean Academy of Medical Sciences, 2003)
Although corticosteroids have been the initial agent for the treatment of inflammatory myopathies (IM), immunosuppressive agents such as azathioprine, methotrexate, cyclophosphamide, or cyclosporine are commonly required to control the disease except mild cases. On the other hand, the efficacy of combination therapy of cyclosporine and methotrexate in severe rheumatoid arthritis has been proven without serious side effects. However, in treatment-resistant myositis, the experience of such a therapy is very limited, and has not been described in refractory polymyositis with anti-Jo-1 antibody. Here, we report a young female patient with recalcitrant polymyositis and anti-Jo-1 antibody who was successfully treated with the combination therapy of cyclosporine and methotrexate. At first, the myositis did not respond to several agents, such as corticosteroid, monthly pulse cyclophosphamide, azathioprine, or cyclosporine. Methotrexate was initially avoided as treatment regimen because of its potential pulmonary toxicity in the case with preexisting lung disease.